Chemical activated grinding of cement rawmaterials and shale by acidic coal mine water - Tosun, Yıldırım İsmail (My University, 2014)
Compliance with envirionmental norms of cement raw materials grinding or clinker grinding, feasible production systems and low cost production facilities are needed in today's moderntechnology, also enable the high capacity production. However, raw materials and chemical nature of them requires avariety of adaptation methods. For this purposei universities and industry needing to work together to provide the basic information required in pilot scale. This study examined the cement raw materials, types of Şırnak limestones, Şırnak marly limestone and marly shale and coal shale. The representative samples werw taken from localareas of Şırnak. 24% high Hardgrove Grinding Index were determined at the chemical activated grinding of samples producing yield. For this purpose, chemical treated and further ground for Şırnak limetone, Şırnak marly shale and coal shale were discussed.